Albert Camus, the Algerian colonialism, terrorism, justice - Carroll, David 1944- (Columbia University Press, 2007)
In these original readings of Albert Camus' novels, short stories, and political essays, David Carroll concentrates on Camus' conflicted relationship with his Algerian background and finds important critical insights into questions of justice, the effects of colonial oppression, and the deadly cycle of terrorism and counterterrorism that characterized the Algerian War and continues to surface in the devastation of postcolonial wars today.